Resposta :
Letra a)
= logb (x/y)
propriedade logaritmo do quociente:
= logb (x) - logb (y)
= - 2 - 3
= - 5 >>> resultado.
Letra b)
= logb (x³ * y²)
propriedade logaritmo do produto:
= logb (x³) + logb (y²)
propriedade logaritmo da potência:
= 3 * logb (x) + 2 * logb (y)
= 3 * (-2) + 2 * 3
= - 6 + 6
= 0 >>> resultado.
Letra c)
= logb (y²/√x)
propriedade logaritmo do quociente:
= logb (y²) - logb (√x)
= logb (y²) - logb (x^½)
propriedade logaritmo da potência:
= 2 * logb (y) - 1/2 * logb (x)
= 2 * 3 - 1/2 * (-2)
= 6 + 2/2
= 6 + 1
= 7 >>> resultado.